2007
DOI: 10.1111/j.1751-9004.2007.00045.x
|View full text |Cite
|
Sign up to set email alerts
|

The Chinese Personality Assessment Inventory as a Culturally Relevant Personality Measure in Applied Settings

Abstract: This paper introduces the development of the Cross-Cultural (Chinese) Personality Assessment Inventory (CPAI) as a culturally relevant measure for personality assessment in collectivistic cultures. In addition to universal personality traits, the CPAI included indigenously derived scales that assessed the relational aspects of personality. We reported three studies that illustrated the usefulness of these indigenous scales in Chinese organizational settings. The Interpersonal Relatedness factor scales on the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 24 publications
2
24
0
Order By: Relevance
“…The forms of interaction involve courteous rituals, exchange of resources, reciprocity, maintaining, and utilizing useful ties, and nepotism (Cheung, et al, 1996;sample item: ''When dealing with institutions, things can work out more smoothly through the connections of friends working inside''). Cheung, Fan, and To (2008) found that senior-level executives scored higher on the Renqing scale than junior-level executives, middle-level executives, and the Hong Kong normative samples. They suggested that business practitioners in the Chinese context might need to understand the cultural-specific standards of social exchange in order to succeed.…”
Section: Emic Relationship-oriented Personality Constructs Of the Cpai-2mentioning
confidence: 95%
“…The forms of interaction involve courteous rituals, exchange of resources, reciprocity, maintaining, and utilizing useful ties, and nepotism (Cheung, et al, 1996;sample item: ''When dealing with institutions, things can work out more smoothly through the connections of friends working inside''). Cheung, Fan, and To (2008) found that senior-level executives scored higher on the Renqing scale than junior-level executives, middle-level executives, and the Hong Kong normative samples. They suggested that business practitioners in the Chinese context might need to understand the cultural-specific standards of social exchange in order to succeed.…”
Section: Emic Relationship-oriented Personality Constructs Of the Cpai-2mentioning
confidence: 95%
“…A series of empirical studies using the CPAI and CPAI‐2 demonstrated the reliability and validity of family orientation and supported its significant explanatory power against career‐related outcome behaviors in the Chinese context beyond that of etic personality dimensions (Cheung, Fan, & To, ; Cheung, Fan, & Yao, ). For instance, Cheung et al () found that MBA students with experience in senior management positions had higher mean scores on the Family Orientation scale than students in junior positions.…”
Section: Family Intrusiveness Family Orientation and Career Decisiomentioning
confidence: 96%
“…Despite the widespread use in mainstream psychology, research in various languages has suggested that five dimensions may or may not be sufficient. Alternative models with larger number of factors in addition to the Big Five (Ashton, Lee, & de Vries, 2014; Cheung, Fan, & To, 2008; Cheung, Van de Vijver, & Leong, 2011; Nel et al, 2012; Valchev, Van de Vijver, Nel, Rothmann, & Meiring, 2013), smaller number of conceptually similar factors to the Big Five (De Raad et al, 2010, 2014; Saucier, Thalmayer, & Bel‐Bahar, 2014; Saucier et al, 2014), as well as different factor structures that do not resemble the Big Five (Saucier, Thalmayer, & Bel‐Bahar, 2014; Saucier, Thalmayer, Payne, et al, 2014) have been identified across a number of languages and cultural samples.…”
Section: The Psycholexical Approachmentioning
confidence: 99%